Hegemoni Pemerintah Negara Sekuler: Diskriminasi terhadap Muslim di Perancis - Gustiani, Mona; A’la, Abd; sholihah, Imroatus (IAIN Syekh Nurjati Cirebon, 2024)
Starting from the government policy that increasingly develops the principle of laicite by issuing several policies that discriminate against Muslims in France. It has led to several cases and realities that have been experienced by Muslims in France. The issuance of the law on March 15, 2004 which has been passed by the French government provides a severe challenge to Muslims there. In addition, in 2020 there was the murder of Samuel Paty by a teenager named Abdoullakh Abouyezidovitc. The murder was carried out on the basis of Samuel Paty teaching freedom of speech to his students using caricatures of the Prophet Muhammad SAW from the satirical magazine Charlie Hebdo. The existence of the law is certainly not in accordance with the aspects of laicite which should be neutral between its relationship with religion and the state. This research uses a qualitative approach and library research as the type of research.